PEMAKNAAN AGAMA MENURUT NARAPIDANA KELAS II A CURUP REJANG LEBONG - M Joko Mulyono (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2016)
Abstract: The purpose of this study is to know about the Making of Religion According Inmates Class II ACurupRejangLebong. Research conducted qualitative, with a phenomenological approach. Who became an informant as a data source is numbered 25 people, comprising leaders of Prison Administration, part spiritual guidance, some prison employees and inmates Penitentiary Class II A CurupRejangLebong the Islamic religion. Then the research data were analyzed using analytical techniques deskriftik. In that study, obtained results and findings are as follows: First. About the Making of Religion diseputar meaning of faith in God, the results show that prisoners in giving meaning of faith in God divides into three categories. First, they interpret that faith in God believe wholeheartedly that God as the Creator of all the entities including humans in it with a power that is infinite, man as a weak creature who must obey and is subject to all the provisions that God ordained, because majbur human nature and do not have the resources and efforts, but the resources and efforts of Allah alone. Secondly, they interpret the faith in God that God is the One who is obligatory to believe and it is believed that he is Kholik, creator of the almighty, God is only entitled to assess and reward of heaven for His creatures who do good and give a reward or punishment of hell for His sinful creatures. While the effort caused by humans is a result of the strength born of man himself. Third, they interpret the faith to God by giving portions and capacity are balanced, in the sense that God is the One almighty creator, Supreme penetu everything related to the creation, but humans have the power to set and give birth usahanyat called by al-kasb, So humans in this understanding is required to make every effort possible but everything God decide. The second is to search in this study are: the Making of the nature of God. The results show. First, they make sense that God has the qualities of his like, has power, Wills, and others, and nature-Sifaat is attached to the Essence of Allah alone, and t is different from the properties owned by limited human, either by time and space. Second, they make sense that God would not have these qualities, moreover these traits inherent in His Essence, because the essence of God is One God, so that God has the nature that God is not One. Implementation from third on the meaning of faith in God and their characteristics in everyday life in prison Class II ACurup Rejang Lebong. From the data I got, was found as a result, changes and effects are quite good, from the construction and touch religious they earn while in prison, in behavior and religious practice, proved the existence of consciousness to perform the five daily prayers, responsible for the task provided, discipline in implementing the obligations, and cooperation among them, although not one hundred percent have at least resulted in changes that lead to increased faith.